Wearing body cameras increases assaults against officers and does not reduce police use of force: Results from a global multi-site experiment. (November 2016) - Ariel, Barak; Sutherland, Alex; Henstock, Darren; Young, Josh; Drover, Paul; Sykes, Jayne; Megicks, Simon; Henderson, Ryan
Police use of force is at the forefront of public awareness in many countries. Body-worn videos (BWVs) have been proposed as a new way of reducing police use of force, as well as assaults against officers. To date, only a handful of peer-reviewed randomised trials have looked at the effectiveness of BWVs, primarily focusing on use of force and complaints. We sought to replicate these studies, adding assaults against police officers as an additional outcome. Using a prospective meta-analysis of multi-site, multi-national randomised controlled trials from 10 discrete tests with a total population of +2 million, and 2.2 million police officer-hours, we assess the effect of BWVs on the rates of (i) police use of force and (ii) assaults against officers. Averaged over 10 trials, BWVs had no effect on police use of force ( d = 0.021; SE = 0.056; 95% CI: –0.089–0.130), but led to an increased rate of assaults against officers wearing cameras (d = 0.176; SE = 0.058; 95% CI: 0.061–0.290). As there is evidence that cameras may increase the risk of assaults against officers, more attention should be paid to how these devices are implemented. Likewise, since other public-facing organisations are considering equipping their staff with BWVs (e.g. firefighters, private security, traffic wardens), the findings on risks associated with BWVs are transferrable to those occupations as well.